Design of Video Transmission with Wi-Fi on Runway Inspection using Jetson Nano and Data Synchronization - Ayman, Raisyafitri; Suparlan, Suparlan; Wahyudi, Johan (Indonesian Journal of Education and Mathematical Science, 2024)
This study aims to facilitate runway maintenance activities by designing a transmission video on an unmanned aerial vehicle (UAV). This design is designed to transmit video in real time via WiFi and provide location information via the integrated GPS data. The evaluation phase is carried out to evaluate the success of the design according to predetermined criteria. In the trial design, the video transmission distance and data transmission speed were tested, as well as the synchronization between GPS and video data. The test results show that the design of this video transmission has not fulfilled all the criteria set. The design can transmit video and synchronize, but there are problems with Jetson Nano so that it cannot carry out remote trials. It is hoped that this design can assist in runway inspection activities using UAVs, as well as provide accurate information via video and GPS data.